Testing on condenser heat exchange and pressure properties - Ong, Ivan Qing Sheng. (2011)
This report is a documentation of my experience while undergoing my final year project. The project explains the performance testing of vapor compression cycle (VCC) and includes the analytical view on the data acquisition.